Model-based control of enzyme yield in solid-state fermentation - Bück, A. (2015)
Solid-state fermentation is gaining increasing importance for the production of high-added value products, for instance enzymes, from agro-industrial by-products. The main difficulty in operating this process in packed-bed bioreactors is the development of temperature and moisture gradients along the reactor length which decrease the overall productivity. In this work a practically relevant feedback control scheme is developed that allows influencing and equalizing the moisture and temperature distributions along the packed-bed bioreactor during solid-state fermentation. This prevents locally critical process conditions which may necessitate the shutdown of the operation of the bioreactor.